The Effect of Acid Hydrolysis Treatment on the Production of Nanocellulose Based on Oil Palm Empty Fruit Bunches - Athanasia Amanda Septevani; Dian Burhani; Yulianti Sampora; Yenni Apriliany Devy; Gita Novi Ariani; Sudirman Sudirman; Dewi Sondari; Khairatun Najwa Mohd Amin (Jurnal Kimia Terapan Indonesia, 2019)
Nanocellulose has been known as promising reinforcing material in various polymer based product resulted to remarkable improvement in mechanical and thermal properties. Hence, studies to date have developed and explored various sources of biomass to produce nanocellulose. The aims of this study are to synthesize and fully characterize nanocellulose obtained from abundantly available oil palm empty fruit bunches via two different methods which are strong (H2SO4) and mild acid (H3PO4) hydrolysis at 50 Â°C for 3.5 hours. Based on the morphological study using Transmission Electron Microscopy, rod like nanocellulose was obtained using strong acid hydrolysis while mild acid hydrolysis produced long filament shape. X-Ray diffraction analysis showed that the degree crystallinity of nanocellulose produced from strong acid hydrolysis was higher which is 96% than that of mild acid hydrolysis recorded with 86%. While the sulphuric acid hydrolysis usually produces lower thermal stability than that of other types acid hydrolysis, surprisingly, in this study, the thermal stability of nanocellulose from strong acid hydrolysis was relatively similar to mild acid hydrolysis due to the formation of single crystal structure affording unique characteristic of the obtained nanocellulose.